Effect of Morin on Arsenic-induced Hepato-Renal Toxicity in Swiss Albino Mice - Priyadarshini, Utkalika; Dash, Jeevan R.; Parija, Subash C.; Mishra, Uma Kanta (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Morin is a bioflavonoid with antioxidant properties. This study was aimed to investigate the protective effects of morin against arsenic induced hepatic and renal injury and hematotoxicity in mice. 24 male Swiss albino mice of 5-6 weeks of age were divided into four experimental groups six mice each, Gr-I (control), Gr-II (Arsenic trioxide @ 3 mg/kg b.wt. p.o. for 28 days), Gr-III (morin @ 50 mg/kg b.wt. p.o. + Arsenic trioxide @ 3 mg/kg b.wt. p.o. for 28 days), Gr-IV (morin @ 100 mg/kg b.wt. p.o. + Arsenic trioxide @ 3 mg/kg b.wt. p.o. for 28 days). In Gr-III and Gr-IV Morin was administered 30 min before oral administration of arsenic trioxide. On 29th day 0.5-1.0 mL blood was collected, and serum was separated and used to determine hepatic marker biomolecules AST and ALT and, renal marker biomolecules creatinine and urea. The serum ALT and AST levels in arsenic intoxicated animals increased as compared to control group, which were attenuated by co-administration with morin. Creatinine and urea level in Gr II was significantly high compared to control animals which was decreased by co-administration with morin. TLC was reduced in arsenic-intoxicated animals, which improved due to co-administration with morin @ 100 mg/kg p.o. Histopathology revealed significant improvement in hepatic and renal histoarchitecture in groups treated with morin @ 100 mg/kg p.o. It is suggested that morin @100 mg/kg p.o is more protective than @50 mg/kg/b.wt. p.o against arsenic-induced hepatic and renal toxicity in Swiss albino mice.